2005
DOI: 10.1080/00207140590927545
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic Analgesia for Chronic Pain in Persons with Disabilities: A Case Series Abstract

Abstract: Thirty-three adults with chronic pain and a disability were treated with hypnotic analgesia. Analyses showed significant pre- to posttreatment changes in average pain intensity that was maintained at 3-month follow-up. Significant changes were also found in pain unpleasantness and perceived control over pain but not in pain interference or depressive symptoms. Hypnotizability, concentration of treatment (e.g., daily vs. up to weekly), and initial response to treatment were not significantly associated with tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 36 publications
10
83
0
Order By: Relevance
“…40,41 Preliminary research suggests that such interventions might also benefit persons with chronic pain and physical disabilities, such as SCI. 42,43 For example, in one preliminary study, 18 individuals with disabilities (including 10 with SCI) were provided with either eight 90-min sessions of a cognitiverestructuring intervention designed to minimize negative cognitions in response to pain ('catastrophizing' responses) or eight 90-min sessions of a control intervention (education about chronic pain). 42 The participants who received cognitive-restructuring reported greater pre to post-treatment decreases in pain intensity than those in the control condition.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Preliminary research suggests that such interventions might also benefit persons with chronic pain and physical disabilities, such as SCI. 42,43 For example, in one preliminary study, 18 individuals with disabilities (including 10 with SCI) were provided with either eight 90-min sessions of a cognitiverestructuring intervention designed to minimize negative cognitions in response to pain ('catastrophizing' responses) or eight 90-min sessions of a control intervention (education about chronic pain). 42 The participants who received cognitive-restructuring reported greater pre to post-treatment decreases in pain intensity than those in the control condition.…”
Section: Discussionmentioning
confidence: 99%
“…Trait theories [41] state that individuals vary in their level of hypnotizability, with individuals high in hypnotic suggestibility responding better to hypnotic suggestions. While there is evidence that level of suggestibility has been significantly related to hypnotic outcomes [15,18], studies have also found that individuals low in hypnotizability can also experience improvements in pain after hypnosis [42][43][44], and some research had found no association between level of hypnotizability and outcome [45,46]. Social-cognitive theories suggest that expectancies, motivation, and environmental cues contribute to an individual's responsiveness to hypnotic suggestions and that improvements are made via cognitive changes that alter the affective components of pain [18,45,47,48].…”
Section: Neurophysiological Mechanisms Involved In Pain Perception Anmentioning
confidence: 99%
“…Trait theories argue that it is related to hypnotizability and the state of hypnosis, whereas social-cognitive models state that it is because of expectancies, motivation, and environmental cues. However, neither model has garnered overwhelming support in clinical studies [18,45,46]. Additional models may need to be developed to better answer these questions, and research will be needed to test these new models.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Jensen et al [43] examined the effects of 10 sessions of standardized script-driven hypnotic analgesia treatment on pain intensity, pain unpleasantness, depression and perceived pain control in 33 patients with chronic pain secondary to a disability. Analyses indicated significant pre-to post treatment improvement in pain intensity, unpleasantness and perceived control over pain lasting 3 months.…”
Section: Journal Of Physiotherapy and Physical Rehabilitationmentioning
confidence: 99%
“…It is possible to be aware of a painful sensation and not be bothered by it. Sometimes it is even possible to experience significant pain and still not seem bothered by it" [43]. c) Post-hypnotic suggestion for extending session benefits to daily life.…”
Section: Individual Sessions Involvedmentioning
confidence: 99%